Hungarian Monitoring, 31 October 1988 . [Magyar rádiófigyelő], 1988. október 31 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - After Friday's demonstration in Prague - Debate on military downsizing in Sweden - Modifying the Soviet constitution; Gorbachev weighed up post-1985 era in his speech on Saturday - Fate of the Gdansk shipyard - Changes “in the air” in Berlin Domestic Affairs: - Károly Grósz receives West German research and technology minister H. Riesenhuber and Austrian ambassador to Hungary - Hungarian premier visits Videoton on its 50th anniversary and discusses questions of contemporary relevance - Reuters director arrives in Budapest; opening local office mentioned during talks - Association of Soviet Friendship Societies awards Imre Pozsgay with Order of Friendship - Most protests against Gabčíkovo-Nagymaros dam on world environment day - Guarding memories: interview with the Institute of Party History director Economy: - International conference on joint East-West companies opens in Budapest - Hungary's second most important partner among developing states is Egypt: the two countries' economic cooperation councils confer Külpolitika: - A pénteki prágai tüntetés után - Haderő csökkentési vita Svédországban - Alkotmánymódosítás a SZU-ban; Gorbacsov szombati beszédében a 85 óta eltelt idő mérlegét vonta meg - A gdanski hajógyár sorsa - Berlini változások a "légtérben" Belpolitika: - Grósz Károly fogadta H. Riesenhuber nyugatnémet kutatási - És technológiai miniszter és Ausztria magyarországi nagykövetét - A magyar miniszterelnök látogatást tett az 50. születésnapját ünneplő Videotonban, ahol időszerű kérdésekről is beszélt - Budapestre érkezett a REUTER igazgatója. Iroda nyitása is szóba került a tárgyalásokon - A Szovjet Baráti Társaságok Szövetsége kitüntette Pozsgay Imrét a Barátság érdemrenddel - A környezetvédelmi világnap alkalmából újabb tiltakozás volt a bős-nagymarosi vízlépcső ellen - Megőrzött emlékezet - Interjú a Párttörténeti Intézet igazgatójával Gazdaság: - Kelet-nyugati vegyesvállalatokkal foglalkozó nemzetközi konferencia kezdődött Budapesten - A fejlődő államok között hazánk második legfontosabb kereskedelmi partnere Egyiptom. Tanácskozott a két ország gazdasági együttműködési tanácsa